If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -20(t + -979) = 20 Reorder the terms: -20(-979 + t) = 20 (-979 * -20 + t * -20) = 20 (19580 + -20t) = 20 Solving 19580 + -20t = 20 Solving for variable 't'. Move all terms containing t to the left, all other terms to the right. Add '-19580' to each side of the equation. 19580 + -19580 + -20t = 20 + -19580 Combine like terms: 19580 + -19580 = 0 0 + -20t = 20 + -19580 -20t = 20 + -19580 Combine like terms: 20 + -19580 = -19560 -20t = -19560 Divide each side by '-20'. t = 978 Simplifying t = 978
| 0.10c+53.10=c | | 45x+25y=150 | | -35+2k=k-4k | | 6x=3x+2y | | -2(x+5)-12=3(10-x) | | (7x+9)=36 | | 5(log(x)+7)=11 | | y-959=24 | | 2g=f+3 | | z-12=25 | | 9x-33=180 | | -2x+6=4x-12 | | 3f=g-4 | | x^7-25x^3=0 | | -100=d+334 | | 7X-4=4X+47 | | 5(x+3)-2(3x+7)=18 | | 3/5x+7=5 | | 91x+16=1895 | | 2x-6=-1+2x | | 672=-8j+56 | | y=2(0.92) | | 15x-11=59 | | y-20=2y-60 | | 6j+18=96 | | 8x-9=65 | | 10x+3=97 | | 8p-7p-4=p-4 | | y-20=2x-60 | | 15=18t+(-3t) | | 6x^3-14x^2-16x= | | -9b-10=-10b-9 |